Dreams and Disillusionment: A Critique of the American Dream in American Fiction - Muttaleb, Fuad Abdul; Mansour, Ashraf Waleed; Shdouh, Ala (Journal of Ecohumanism, 2024)
This study examines the vanity and consequences of the American Dream as depicted in four novels: Upton Sinclair's The Jungle, Jack London's The Iron Heel, F. Scott Fitzgerald’s The Great Gatsby, and John Steinbeck's The Grapes of Wrath. A socio-political analysis of these authors and their works exposes the hollow nature of the dream. The Jungle is discussed from a racial and economic perspective, highlighting the plight of Jurgis and his Lithuanian family who are disillusioned in their pursuit of success. The Iron Heel is examined politically, showcasing the struggle between the capitalist class and workers. In The Great Gatsby, Fitzgerald presents a social satire, critiquing the death of American ideals sacrificed for materialism. The Grapes of Wrath analyzes the American Dream through the Joad family's migration and exploitation. This work studies and compares the representation of the American Dream in these novels, referencing texts, socio-economic contexts, and relevant critical works.